Dolphin boy - Bertagna, Julie; Chapman, Chris (Mammoth London, 1999)
A boy who won't speak meets a lost dolphin. Trapped in loneliness, a bond of friendship grows between them that leads the way to happiness and freedom for both the boy and the dolphin.